Estudos da camada limite atmosférica com o modelo WRF: fenologia de florestas temperadas, turbulência e relevo - Battisti, Adriano (2018)
In this work, we have studied the behavior of surface variables and the Atmospheric Boundary Layer (CLA) during the leaf emergence (EF) at the temperate forests of the northeast United States of America. We have used the Weather Research and Forecasting (WRF) model and observational data from four towers of the region. There is a climatological characteristic on the simulations because they cover a 13 years period with hourly outputs. We have analyzed, in general, the interannual, seasonal and daily cycle behaviors of the sensible heat (H) and latent heat (LE) fluxes, with the aim to understand the phenology of these forests. This evaluation was made for observed and modeled data, and the model efficiency was analyzed according to each studied site. We have aimed, also, to find an identifier of the spring onset from CLA variables and its tendency over the years. We have compared model outputs for several different land uses. In addition, the fluxes dependence on turbulence and topography was analyzed. In general, the model have superestimated the surface fluxes magnitude both in day and at night. Also, in the different seasons, specially H during the summer at the deciduous forests. The variables associated with sensible heat, like temperature, specially their daily rate, were the best parameters to be a objective identifier for EF, considering CLA mean variables. WRF have had problem to simulate the humidity near EF, which can be associated to the fact that the model does not update phenology rapidly enough to describe the sharp spring transition. This have mined the model ability to identify EF date, which shows the necessity of phenological reproduction improvement. The trend toward earlier EF dates seems to be associated with more precipitation, but not with temperature. Unlike, spring intensity has showed dependence on this last variable. Several dependencies were observed for H but not for LE. Turbulence and topography have modulated the simulated H error but a relation with LE was not observed.